CRYSTAL STRUCTURE OF HYPERZIRCONIUM SULFATE ANALOGUE OF EUDIALYTE - Rastsvetaeva R.K.; Verin I.A.; Chukanov N.V. (My University, 2006)
Eudialyte is the common mineral of alkaline agpaitic massifs. In some cases, it occurs as a major mineral and important carrier of some rare elements. The crystal chemical formula of typical eudialyte contains six Ca (as a six-membered octahedral ring) and three Zr atoms p.f.u. However, eudialytes formed in specific conditions have different stoichiometry. For example, hypercalcium analogues of eudialyte (feklichevite, golyshevite, mogovidite) were found in pegmatites related to alkaline ultrabasic rocks. These minerals typically contain 8–10 Ca atoms p.f.u., with excess Ca incorporated in one or two extraframework sites.
Keywords: eudialyte; hyperzirconium